2002
DOI: 10.1021/jp0115289
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Photochromism and Thermochromism in Nitroso Monomer−Dimer Equilibrium

Abstract: Monomer-dimer equilibrium of nitroso compounds was investigated in the solid state under cryogenic photochemical conditions. It was found that nitroso dimers can be UV-photolytically converted to nitroso monomers at 12 K, and reverted to dimers by visible light irradiation or warming above 170 K. Such a photothermal "chemical switch", by which it is possible to break the chemical bond between two nitrogen atoms and bind them again, could eventually be used in supramolecular self-assembly systems. The reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The observed temperature of this thermal transition from monomer to dimer was between 265 K and 275 K. The photolysis of 1 has been repeated at different temperatures, and it was found that the highest temperature at which this compound undergoes photochromic dissociation is 245 K. This temperature is much higher than in the case of previously observed photoreaction of p-bromonitrosobenzene (170 K). 2 The transformation cycle that includes photodissociation followed by thermal redimerization was repeated five times. Relative intensity of the 1503 cm −1 band assigned to the monomer NO stretching vibration was more or less recovered after an each cycle ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed temperature of this thermal transition from monomer to dimer was between 265 K and 275 K. The photolysis of 1 has been repeated at different temperatures, and it was found that the highest temperature at which this compound undergoes photochromic dissociation is 245 K. This temperature is much higher than in the case of previously observed photoreaction of p-bromonitrosobenzene (170 K). 2 The transformation cycle that includes photodissociation followed by thermal redimerization was repeated five times. Relative intensity of the 1503 cm −1 band assigned to the monomer NO stretching vibration was more or less recovered after an each cycle ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…2 Since these processes include breaking and rebinding the azodioxide nitrogen-nitrogen bonds, the system represents a sort of molecular OFF-ON switch, (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Monomeric molecules can be prepared within the crystalline solids by photodissociation of azodioxy dimers. Photolysis of different azodioxides to the corresponding monomers has been observed in crystals when they are cooled to cryogenic temperatures (10-12 K), and irradiated by UV light (254 nm) [26,[29][30][31]40]. The process can be followed even visually because the monomers are coloured blue or green, while most of the azodioxides are colourless or yellow.…”
Section: Experimental and Conceptual Modelmentioning
confidence: 99%
“…15 Under cryogenic conditions in crystals, azodioxides undergo photodissociation to monomers, and in turn, by warming above some critical temperature redimerization occurs. 16 Therefore, this system represents a sort of molecular OFF-ON switch. Since the strength of the azodioxide (O)N=N(O) bond is comparable with the average hydrogen bond, 17 the property of nitrosoarenes to dimerize could be used to build novel supramolecular architectures with special properties of intelligent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides gaining valuable new insights into the dimerization properties of Cnitrosoarenes, these supramolecular systems provide potential for novel applications. Due to the photo-chromic and thermochromic behavior of Cnitrosoarenes in solid state, 16 layers on an Au(111) surface and AuNPs aggregates formed via azodioxide bonds could eventually be triggered by light or heat. In addition, the presence of sulphur groups at outer surface of the SABs formed on an Au(111) may provide a simple means for the fabrication of metallic layers with applications in molecular electronics.…”
Section: Introductionmentioning
confidence: 99%